2007
DOI: 10.1177/1741143207075390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structured Self-reflection on the Development of Authentic Leadership Practices among Queensland Primary School Principals

Abstract: This article reports on research that explored the concept of authentic leadership with seven principals of Catholic primary schools in Brisbane, Australia. Recent developments in leadership theory have promoted the concept of authentic leadership for addressing the leadership demands associated with our seemingly ever-changing and unpredictable, if not chaotic, world. In particular, authentic leaders are said to act in accordance with their personal values and convictions thereby building essential credibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 13 publications
0
53
0
7
Order By: Relevance
“…Robertson (2005) explains that if an individual is capable of operating in the domain of generative paradox they will gain insights through reflection about their behaviour that will enable them to learn and develop. Previous research (Begley, 2007;Branson, 2007;Muijs and Harris, 2004) with teachers has also stressed the importance of reflection if they are to develop their leadership capability in the classroom. Yet this group of teachers did not associate reflection with effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robertson (2005) explains that if an individual is capable of operating in the domain of generative paradox they will gain insights through reflection about their behaviour that will enable them to learn and develop. Previous research (Begley, 2007;Branson, 2007;Muijs and Harris, 2004) with teachers has also stressed the importance of reflection if they are to develop their leadership capability in the classroom. Yet this group of teachers did not associate reflection with effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Sınıf içinde öğretmen liderliği, öğrencinin başarısını pozitif yönde etkilemede ve öğrenciyle pozitif ilişkinin kurulmasında oldukça önemli bir yer almaktadır (Argyris and Schon, 1996). Liderlik alanyazınında öğretmenin sınıf içinde liderliği ile ilgili çok az çalışmanın olduğu görülmektedir (Can, 2006;Cheng, 1994;Çağlar, Yakut ve Karadağ, 2005;Branson, 2007;Begley, 2007). Bu çalışma, öğretmenlerin sınıf içinde liderlik davranışlarının etkililiğini araştırmaktadır.…”
Section: öZetunclassified
See 1 more Smart Citation
“…Moreover, the practice of authentic leadership depends on leaders having high self-awareness of their values; this helps ensure that they act in alignment with their convictions. A deeply structured process of self-reflection is one way of increasing principals' explicit self-knowledge (Branson, 2007).When designing preparation and professional development programs for principals, faculty must consider how to strengthen the link between personal consciousness and professional practice and also enhance their principals' moral courage to overcome any hindrances to authentic leadership.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…In addition, Branson (2006) focuses on sharpening leaders' knowledge, skills and abilities that promoted learning through a deeply structured reflective process. Interestingly, May's (2011) research undertaken with leaders of children's services suggested that the skills required by the next generation of leaders consisted of: creativity, ingenuity and skills of collaboration; entrepreneurial/business planning skills; ability to marshal resources and make best use of professional expertise; and confidence and courage to challenge orthodox solutions and to implement change in the face of opposition from the professional establishment.…”
Section: Leadership Skillsmentioning
confidence: 99%